W63+ and W64+ ionization by protons and photons. (29th January 2015) - López, S D; Randazzo, J M; Picca, R Della; Colavecchia, F D
Abstract: In this work we investigate the ionization by proton impact, and photo ionization, involving highly charged ions of W, in particular the Ne-like W 64+ and Na-like W 63+ which are more likely to appear in ITER plasma. Total cross sections are calculated in the continuum-distorted-wave-eikonal-initial-state (CDW-EIS) approximation for ion-impact, while two completely different methods are used for photoionization: a perturbative dipolar aproach and the recently introduced Sturmian model.